Education And Vaccination Are Required to Prevent the Spread Of COVID-19 In the Christian University Papua Environment - Disabella Dayera; Roger Tabalessy; Rosa Sapulette; Ivonne M. Leiwakabessy; Melani Manurung; Lili Sarce Joi Sapari; Jean Anthoni (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
The COVID-19 vaccination aims to make a person's immune system able to recognize and quickly fight the virus that causes infection, reducing the pain and death rates caused by this virus. As for supporting the government's program of providing vaccinations to the community, the Sorong Papuan Christian University (UKiP), in collaboration with the Tanjung Kasuari Health Center, has conducted mass vaccinations for the entire UKiP Sorong academic community, consisting of employees, lecturers, students, alumni, and the community. Implementing the COVID-19 mass vaccination activity was carried out twice, with the first stage being attended by 130 people, and the second stage being followed by 150 people. This shows the awareness shared by the campus and the community in trying to break the chain of the spread of the COVID-19 virus and assist the government in restoring the social and economic conditions of the Sorong City area affected by the pandemic.